Gender and Precarious Research Careers 2018
DOI: 10.4324/9781315201245-3
|View full text |Cite
|
Sign up to set email alerts
|

The gendered diversification of academic career paths in comparative perspective

Abstract: Higher education has many variants, and the situation of academic staff varies considerably across and within countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Recent studies have shown the relevance of deep organizational changes that have reshaped scientific work and careers in academic and research institutions in the last decades. These transformations, both globally and locally, are characterized by new forms of governance in academic and research institutions, redesigned practices and research schedules in academic work, redefined competition mechanisms, and the relevant effects on scientific career paths (Felt 2009(Felt , 2016Le Feuvre et al 2018).…”
Section: Unveiling New (And Old) Gender Inequalities In Academiamentioning
confidence: 99%
“…Recent studies have shown the relevance of deep organizational changes that have reshaped scientific work and careers in academic and research institutions in the last decades. These transformations, both globally and locally, are characterized by new forms of governance in academic and research institutions, redesigned practices and research schedules in academic work, redefined competition mechanisms, and the relevant effects on scientific career paths (Felt 2009(Felt , 2016Le Feuvre et al 2018).…”
Section: Unveiling New (And Old) Gender Inequalities In Academiamentioning
confidence: 99%
“…This is mainly due to weak and residual support in managing employment instability, typical of Southern European welfare systems; to the higher risk of being trapped in temporary and low-paid job positions; and to the general lack of competitive job options outside of academia (Bozzon et al, 2017). In contrast to other European countries, such as Germany, Switzerland, Belgium and the Netherlands, where doctoral qualifications are recognized and rewarded on the non-academic labour market, in Italy there is a lack of qualified job options outside of academia for PhD holders, who therefore have limited opportunities to deploy the knowledge and skills previously acquired (Le Feuvre et al, 2019). The institutional discourse on the modernization of the university, and on the need to open the floodgates to young researchers, therefore, comes up against a situation that remains one of -if not the -most problematic across Europe.…”
Section: 'Young On Paper': the Italian Reform Of The University Recrumentioning
confidence: 93%
“…In such a way the only permanent positions are those at the top of the academic hierarchy, similarly to countries with a Humboldt tradition of academic chairs (e.g. Austria, Germany, Switzerland and Belgium) (Le Feuvre et al, 2019).…”
Section: 'Young On Paper': the Italian Reform Of The University Recrumentioning
confidence: 99%
“…It's also well known that higher educated are more likely to respond to surveys (see f.e. Le Feuvre et al 2018). Nevertheless, one may also think that this echoes the tertiarisation of the sector 12.…”
Section: Inquiry and Respondents Samplementioning
confidence: 99%